The effects of L-carnitine on respiratory function tests in children undergoing chronic hemodialysis - Kavukçu, Salih; Türkmen, Mehmet; Salman, Şinasi; Önvural, Banu; Oktay, Gülgün; Karaman, Özkan; Çevik, Necla T. (The Turkish Journal of Pediatrics, 1998)
Respiratory functions are affected during hemodialysis. Ultrafiltration rate, acid-base balance and the strength of respiratory muscles have been suggested as important factors in adults undergoing chronic hemodialysis. L-carnitine is crucial for energy producing utilization fatty acid and, possible amino acids. Carnitine treatment has been associated with hypertrophy of type I muscle fibers. Carnitine supplementation in non-dialysis patients increases exercise tolerance. Eventually, administration of L-carnitine to adult hemodialysis patients improves exercise capacity, energy metabolism and muscle mass. This study was performed to investigate the chronic effects of L-carnitine treatment on respiratory functions in children receiving chronic hemodialysis therapy. Predialytic and postdialytic respiratory function tests were performed in ten children with end-stage renal disease before and after a three-month L-carnitine treatment period. The mean age was 12 ± 4 years. L-carnitine was administered at a dose of 20 mg/kg intravenously at the end of each hemodialysis session. Mean predialytic serum carnitine values before and after the carnitine treatment period were 21.8 ± 3 and 132.0 ± 48.5 mmol/L, respectively, and the increase was significant (p < 0.05). Respiratory function tests performed just before the carnitine treatment period implied bronchospasm that was clinically vague and could only be detected by a significant decrease in FEV1/FVC, PEF and FEF25-75 values (p < 0.05). Nevertheless, at the end of the three-month carnitine therapy period these respiratory function parameters did not show any significant variation. Hence, It is implied that carnitine therapy might have prevented the subclinic bronchospasm that developed in children during hemodialysis.